Reciprocal repulsions instruct the precise assembly of parallel hippocampal networks - Pederick, Daniel T.; Lui, Jan H.; Gingrich, Ellen C.; Xu, Chuanyun; Wagner, Mark J.; Liu, Yuanyuan; He, Zhigang; Quake, Stephen R.; Luo, Liqun (Science (American Association for the Advancement of Science), 2021)
Brain circuits established during development can be overlapping or parallel as needed. Pederick et al. analyzed how parallel circuits in the mouse medial and lateral hippocampus develop without getting tangled up. Regulated expression of the cell surface molecules teneurin-3 (Ten3) and latrophilin-2 (Lphn2) keeps confusion at bay. Together, these factors act as a membrane-bound ligand-receptor pair with repulsive outcomes, and they are able to destabilize a nascent but incorrect axon-target interaction. Individually, they each mediate homophilic attraction as axons search for their favored targets. Science, abg1774, this issue p. 1068 Multifunctional cell surface proteins instruct axons in search of targets as mouse hippocampal neuronal networks develop. Mammalian medial and lateral hippocampal networks preferentially process spatial- and object-related information, respectively. However, the mechanisms underlying the assembly of such parallel networks during development remain largely unknown. Our study shows that, in mice, complementary expression of cell surface molecules teneurin-3 (Ten3) and latrophilin-2 (Lphn2) in the medial and lateral hippocampal networks, respectively, guides the precise assembly of CA1-to-subiculum connections in both networks. In the medial network, Ten3-expressing (Ten3+) CA1 axons are repelled by target-derived Lphn2, revealing that Lphn2- and Ten3-mediated heterophilic repulsion and Ten3-mediated homophilic attraction cooperate to control precise target selection of CA1 axons. In the lateral network, Lphn2-expressing (Lphn2+) CA1 axons are confined to Lphn2+ targets via repulsion from Ten3+ targets. Our findings demonstrate that assembly of parallel hippocampal networks follows a “Ten3→Ten3, Lphn2→Lphn2” rule instructed by reciprocal repulsions.